Atrophy of cerebellum Crus I indicates poor outcome of cochlear implantation in the elderly - Jun Yup Kim; Dongyeop Kim; Juchan Jung; Beomseok Sohn; Kyung Min Kim; Jae Young Choi; Seong Hoon Bae (Scientific Reports)
Abstract Cochlear implantation (CI) is a highly effective treatment for profound hearing loss in elderly individuals, including those with ARHL. However, factors influencing the success of CI in the elderly population are not fully understood. Hence, we sought to investigate the association of regional cerebellar gray matter volume with effectiveness of CI in the elderly. This retrospective cross-sectional study included CI implantees and healthy controls aged ≥ 70 years. We used voxel-based morphometry to investigate the cerebellar gray matter associated with speech perception outcome in the CI group. Among the study participants, cerebellar gray matter volume loss, particularly in the Crus I region, was associated with poorer CI outcomes. Notably, this association was stronger than that observed for the duration of hearing deprivation (DoD). Moreover, the degree of cerebellar atrophy and DoD were found to be independent of each other. No significant correlation was found between the age of the implant and CI outcomes. The findings suggest that cerebellar gray matter atrophy, specifically in the Crus I region, may serve as a predictor of poor outcomes following cochlear implantation in elderly individuals. These results underscore the importance of assessing cerebellar volume loss alongside other factors when counseling elderly patients considering CI.